Behaviour of Parallel Coupled Microstrip Band Pass Filter and Simple Microstripline due to Thin-Film Al2O3 Overlay - S. B. Rane; Vijaya Puri (Active and Passive Electronic Components)
The X-band behaviour of a seven-section parallel-coupled microstrip band pass filter and microstripline due to thin-film Al2O3 overlay of different thickness is reported in this paper. This Al2O3 film can give a homogeneous overlay structure. There is a substantial increase in the bandwidth due to the overlay, the pass band extending towards higher frequency side. In most of the cases, an increase in the pass band transmittance of a microstripline also increases due to a thin-film Al2O3 overlay, especially for frequencies less than 9.0 GHz. At higher frequencies, random variations are observed. It is felt that thin-film overlays can be used to modify the microstripline circuit properties, thereby avoiding costly and time consuming elaborate design procedures.